2005
DOI: 10.1128/iai.73.7.4451-4453.2005
|View full text |Cite
|
Sign up to set email alerts
|

Structural Diversity of Streptokinase and Activation of Human Plasminogen

Abstract: The ␤ domain of streptokinase is required for plasminogen activation and contains a region of sequence diversity associated with infection and disease in group A streptococci. We report that mutagenesis of this polymorphic region does not alter plasminogen activation, which suggests an alternative function for this molecular motif in streptococcal disease.Streptokinase (SK) is a plasminogen activator secreted by group A, C, and G streptococci. SK contributes to streptococcal virulence by generating plasmin, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 19 publications
4
12
0
Order By: Relevance
“…This suggests that variation within the β domain of these proteins may be responsible for the observed differences in plasminogen activation activities. Lizano and Johnston (42) have suggested that sequence polymorphism in the β-domain has little affect on plasminogen activation. The recombinant streptokinase produced from SF13013 (containing a cluster 2a ska allele) in that study displayed soluble plasminogen activation activity.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that variation within the β domain of these proteins may be responsible for the observed differences in plasminogen activation activities. Lizano and Johnston (42) have suggested that sequence polymorphism in the β-domain has little affect on plasminogen activation. The recombinant streptokinase produced from SF13013 (containing a cluster 2a ska allele) in that study displayed soluble plasminogen activation activity.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the two amino acid residues identified to be relatively vital for 170 loop functioning, namely Pro 177 and Lys 180 , are phylogenetically conserved across the various streptokinase allelic variant "classes" (Fig. 6) despite the generally diverse sequence heterogeneity in this region of streptokinase (34,35). This suggests the evolutionary significance of these amino acid residues in the 170 loop that impart high catalytic turnover to SK⅐plasmin.…”
Section: Steady-state Kinetics Of Plasminogen Activation By Equimolarmentioning
confidence: 92%
“…Recombinant plasmids were used to transform Escherichia coli, and recombinant polypeptides were expressed as fusions with glutathione S-transferase (GST). Recombinant fusion polypeptides were purified by glutathione-Sepharose affinity chromatography (25). The primers used for PCR amplification are listed in Table S2 at http://www.nymc.edu/hotfiles/s3pdebra_bessen.pdf.…”
Section: Methodsmentioning
confidence: 99%